Analysis of Factors Influencing Tax Avoidance in Energy Sector Companies Listed on the Indonesia Stock Exchange - Setyawati, Wiwit; Akhsani, Novi; Nurbaeti, Nurbaeti (Jurnal Multidisiplin Sahombu, 2025)
Tax avoidance in the energy sector has become a pressing issue due to its substantial impact on state revenues and the public’s trust in the tax system. In Indonesia, this concern is heightened by the sector’s strategic role in the national economy and its frequent involvement in aggressive tax planning practices, which, while legal, often undermine the spirit of tax regulations. This study investigates the factors influencing tax avoidance practices in companies operating within the energy sector and listed on the Indonesia Stock Exchange. The research focuses on three independent variables: company risk, capital intensity, and sales growth. Employing a quantitative associative method, the study utilizes secondary data collected from annual financial reports and applies panel data regression analysis using statistical software. The sampling was conducted through a purposive approach to ensure relevance and data consistency. The findings reveal that, collectively, the three variables have a significant impact on tax avoidance. However, on an individual basis, company risk and sales growth do not show a significant effect, whereas capital intensity demonstrates a significant negative influence on tax avoidance behavior. These results suggest that investment in fixed assets plays a vital role in reducing tax burdens legally. This research provides empirical evidence supporting the relevance of financial structure in understanding corporate tax planning within a regulated environment.